2017
DOI: 10.1080/15476286.2017.1416278
|View full text |Cite
|
Sign up to set email alerts
|

snoRNAs associate with mRNA 3′ processing complex: New wine in old bottles

Abstract: 3' end processing is required for the maturation of all eukaryotic RNAs. Current model suggests that canonical mRNA 3' processing is carried out exclusively within a protein complex termed mRNA 3' processing complex. In a recent study, by using RNA-biotin based pull-down assay and high-throughput sequencing, we reported that a subset of small nucleolar RNAs (snoRNAs) were physically associated with this macromolecular machinery. Through detailed characterization of one of these snoRNAs, SNORD50A, we revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Further analysis showed that U1 snRNA is the most abundant and significant non-coding RNAs (ncRNA) interacting with sequences near PASs (Figure 1(b)). Additionally, consistent with the previous finding that a subset of snoRNAs associate with mRNA 3ʹ processing complex [35,36], specific snoRNA-PAS interactions were also detected (Supplemental Table 3). Given that the interactions of U1 snRNAs with PASs were the most abundant and significant, we wished to focus on U1 in this study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Further analysis showed that U1 snRNA is the most abundant and significant non-coding RNAs (ncRNA) interacting with sequences near PASs (Figure 1(b)). Additionally, consistent with the previous finding that a subset of snoRNAs associate with mRNA 3ʹ processing complex [35,36], specific snoRNA-PAS interactions were also detected (Supplemental Table 3). Given that the interactions of U1 snRNAs with PASs were the most abundant and significant, we wished to focus on U1 in this study.…”
Section: Resultssupporting
confidence: 90%
“…We have previously shown that non-coding RNAs (ncRNAs), such as small nucleolar RNAs (snoRNAs), are associated with mRNA 3ʹ processing protein complex [35,36], which prompted us to investigate whether any ncRNA regulates mRNA 3ʹ processing through RNA-RNA interaction. To address this, we performed PAS-CLASH (PolyA site-Crosslinking, Ligation and Sequencing of Hybrid) experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, direct interactions between snoRNAs and pre-mRNAs as well as further processing of snoRNAs into miRNAs and shorter RNAs have emerged as new functions of snoRNAs [[10], [11], [12], [13]]. Here we review a new, so far understudied facet of snoRNA biology: the interaction of snoRNAs, mostly C/D box snoRNAs, with viruses.…”
Section: Snornas Are a Highly Expressed Class Of Non-coding Rnasmentioning
confidence: 99%
“…The role of noncoding RNAs in both 3′ end processing and DDR has not been extensively studied. Recently, a small nucleolar RNA (snoRNA), normally associated with rRNA maturation, was shown to compete with CpA component Fip1 for binding to AAUAAA signal (Huang et al, ; J. Shi, Huang, Huang, & Yao, ). SNORD50A inhibits mRNA 3′ processing by blocking the Fip1‐poly(A) site interaction, and SNORD50A depletion changed APA profiles genome‐wide.…”
Section: Alternative Polyadenylationmentioning
confidence: 99%